2023
DOI: 10.1021/jacs.3c03259
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Ionic-Liquid-Based Electrolyte Enables Efficient Electro-reduction of CO2 over Bulk Metal Electrodes

Abstract: Using bulk metals as catalysts to get high efficiency in electro-reduction of CO 2 is ideal but challenging. Here, we report the coupling of bulk metal electrodes and a ternary ionic-liquid-based electrolyte, 1-butyl-3-methylimidazolium tetrafluoroborate/1-dodecyl-3-methylimidazolium tetrafluoroborate/MeCN to realize highly efficient electro-reduction of CO 2 to CO. Over various bulk metal electrodes, the ternary electrolyte not only increases the current density but also suppresses the hydrogen evolution reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Molecular-level electrolyte design holds great promise as a strategy for improving the selectivity, efficiency, and stability of electrochemical processes. This is because of the recognized importance of fundamental, intermolecular interactions in governing the structure of the electrochemical double layer and the reaction-diffusion region near electrodes in which electrochemical and electrocatalytic processes take place. , Modifications to the structure and composition of these critical microenvironments have been demonstrated to result in dramatic changes in chemical reaction outcomes, particularly in the arena of electrosynthetic work …”
Section: Introductionmentioning
confidence: 99%
“…Molecular-level electrolyte design holds great promise as a strategy for improving the selectivity, efficiency, and stability of electrochemical processes. This is because of the recognized importance of fundamental, intermolecular interactions in governing the structure of the electrochemical double layer and the reaction-diffusion region near electrodes in which electrochemical and electrocatalytic processes take place. , Modifications to the structure and composition of these critical microenvironments have been demonstrated to result in dramatic changes in chemical reaction outcomes, particularly in the arena of electrosynthetic work …”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely studied categories of ionic liquids in electrochemical CO 2 reduction is ionic liquids with imidazolium-derived cations. Since the first report of using a 1,3-diakylimidazolium ionic liquid for CO 2 reduction to CO with unprecedently low overpotential, numerous studies have been performed to understand how imidazolium cations accelerate CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of ionic liquids can greatly improve the solubility of CO 2 and ensure the effective supply of CO 2 in the ECR process, thus inhibiting the hydrogen evolution reaction (HER) and improving the catalytic activity and selectivity of ECR. [37][38][39][40][41] Therefore, we tested the ECR catalytic performance over the Cu/Zn-CP-1-30 electrode using electrolytes with different concentrations of [Bmim]PF 6 /MeCN at −2.5 V vs. Ag/ Ag + . It can be observed that the FE of CO changed with [Bmim] PF 6 content in the electrolytes (Fig.…”
Section: Resultsmentioning
confidence: 99%